Formation and Characterization of a Stable Monolayer of Active Acetylcholinesterase on Planar Gold - Correira, Joshua M (Langmuir : the ACS journal of surfaces and colloids, 2022)
Enzyme activity is the basis for many biosensors where a catalytic event is used to detect the presence and amount of a biomolecule of interest. To create a practical point-of-care biosensor, these enzymes need to be removed from their native cellular environments and immobilized on an abiological surface to rapidly transduce a biochemical signal into an interpretable readout. This immobilization often leads to loss of activity due to unfolded, aggregated, or improperly oriented enzymes when compared to the native state. In this work, we characterize the formation and surface packing density of a stable monolayer of acetylcholinesterase (AChE) immobilized on a planar gold surface and quantify the extent of activity loss following immobilization. Using spectroscopic ellipsometry, we determined that the surface concentration of AChE on a saturated Au surface in a buffered solution was 2.77 ± 0.21 pmol cm-2. By calculating the molecular volume of hydrated AChE, corresponding to a sphere of 6.19 nm diameter, divided by the total volume at the AChE-Au interface, we obtain a surface packing density of 33.4 ± 2.5% by volume. This corresponds to 45.1 ± 3.4% of the theoretical maximum monolayer coverage, assuming hexagonal packing. The true value, however, may be larger due to unfolding of enzymes to occupy a larger volume. The enzyme activity and kinetic measurements showed a 90.6 ± 1.4% decrease in specific activity following immobilization. Finally, following storage in a buffered solution for over 100 days at both room temperature and 4 °C, approximately 80% of this enzyme activity was retained. This contrasts with the native aqueous enzyme, which loses approximately 75% of its activity within 1 day and becomes entirely inactive within 6 days